Brief Acceptance and Commitment Group Therapy for Nursing Home Staff: Effects on Stress, Performance, and Quality of Life - Annisa Rahmalia; Yudiana Ratnasari (Universitas Ahmad Dahlan, 2021)
Staff working in nursing homes holds important roles for caregiving older adults, yet they are prone to experiencing high stress due to high demands at work. Two core processes in Acceptance and Commitment Therapy (ACT): personal values and committed action offers new strategies for nursing home staff to create a more positive attitude, thus potential in improving nursing home staff’s general mental health. This study explores the effects of brief-ACT on psychological flexibility, work stress, in-role performance, and quality of life among nursing home staff. Therapy was conducted in a group setting, emphasizing personal values and committed action core processes, with quantitative measurements administered in pretest-posttest design. Participants also answered open-ended questions for qualitative results regarding with effects of the group therapy. Results showed statistically significant effects of Brief-ACT for psychological flexibility, in-role performance, and quality of life, while the decrease in work stress was not statistically significant. In addition, qualitative themes coded from open-ended questions reported positive experiences related to the group therapy. This study provides initial findings regarding ACT feasibility among nursing home staff, particularly related to personal values and committed action core processes. Keywords: ACT, nursing home staff, values, committed action, work stress.